Dakwah Message in Youtube Channel Muhammad Faizar Official (Case Study on Mount Slamet Expedition) - Surya, Surya; Efendi, Erwan (JASNA : Journal For Aswaja Studies, 2024)
This research aims to discover the da'wah messages on Muhammad Faizar's Official YouTube channel. This research uses a qualitative descriptive research method. This type of research is used to discover and understand research procedures that produce descriptive data in the form of written or spoken words from research subjects and observable behaviour. Research involves text, video, images and so on so that you can find out the content of thoughts and meanings related to a particular social context. Therefore, in this discussion, Ustadz Muhammad Faizar conveyed the Sunnahs that Rasulullah SAW adhered to when carrying out travel activities, such as leaving the house to recite the tawakal prayer (Bismillaahi tawakkaltu 'alallaah, laa haula wa laa quwwata illaa billaah), passing over hills. The road says "Allahu Akbar" and the road down "Subhanallah". The informant also said climbing mountains is sunnah because climbing mountains is a travelling activity. It also discusses the myths found on Mount Slamet, such as the myth of the Sri Kedasih bird in Samarantu. Discussion of the Pos Slamet Cave is seen from an Islamic perspective by the Al-Qur'an and As-Sunnah. By focusing on the da'wah messages conveyed in the context of the Mount Slamet expedition, this research contributes to understanding da'wah practised in travel or safari situations, which aligns with the sunnah practices taught in Islam.